Population Growth of Fall Armyworm, Spodoptera frugiperda Fed on Cereal and Pulse Host Plants Cultivated in Yunnan Province, China - Kifle Gebreegziabiher Gebretsadik; Ying Liu; Yanqiong Yin; Xueqing Zhao; Xiangyong Li; Fushou Chen; Yong Zhang; Julian Chen; Aidong Chen (Plants, 2023)
The fall armyworm, Spodoptera frugiperda is a major agricultural pest in China, and has migrated from its continuous breeding area to other parts of China. In our study, the biological behaviors of S. frugiperda fed on maize, wheat, barley, faba beans, and soya beans were evaluated in a growth chamber. Results indicated that maize-fed S. frugiperda larvae performed well, as evidenced by shorter larva-adult periods, adult pre-oviposition period (APOP), total pre-oviposition period (TPOP), and generation time (T), and a higher survival rate, intrinsic (r) and finite (λ) rate of increase, and net reproductive rate (Ro), However, S. frugiperda larvae performed weakly when fed barley and faba bean plants, as indicated by lower survival rates, r, and λ, and longer pre-adult period, TPOP, and T. A heavier pupal weight of both sexes was recorded on faba beans (0.202 g) and a lighter weight on barley (0.169 g). Fecundity was higher when fed faba beans and maize, and lower when fed wheat and barley. Thus, maize was the most optimal and barley was the least optimal host plant, followed by faba beans, for S. frugiperda larvae growth and development. This study enhances our knowledge of S. frugiperda in these host plants and can help in the design of management approaches.